Case Report: Unilateral uterine torsion in a non-pregnant Siberian-Husky—clinical insights and implications for reproductive management - Ciornei, Ștefan Gregore; Roșca, Petru; Pașca, Aurelian-Sorin; Baisan, Radu Andrei; Ciubotariu, Alexandra (Frontiers in Veterinary Science, 2025)
Uterine torsion is a rare condition in dogs, typically associated with pregnancy or uterine pathology. A 5-year-old, female intact, Siberian-Husky presented with a history of lethargy and constipation for 3 days. Physical examination revealed pale mucous membranes and a firm, painful abdomen. Abdominal imaging revealed a thickened uterine body wall with an increased volume of mixed anechoic and heterogeneous echoic intrauterine content. Exploratory laparotomy confirmed the 360-degree torsion of the left uterine horn, and due to the extensive lesions ovariohysterectomy was deemed necessary. Postoperative clinical evaluation indicated ongoing signs of impaired oxygen delivery warranting hemotransfusion, following which progressive stabilization and complete clinical recovery was achieved. Histopathological examination showed diffuse uterine necrosis due to hypoxia from venous stasis, with inflammatory infiltrate of neutrophils, macrophages, and lymphocytes. This report contributes to the limited veterinary literature on uterine torsion in non-pregnant bitches and underscores the importance of including it in the differential diagnosis, even in young patients or when other reproductive pathology is not evident, where a lack of predisposing factors may reduce clinical suspicion. It clearly illustrates how an acute reproductive emergency can abruptly and permanently preclude any future reproductive potential from an otherwise healthy animal.